Immigrant voters, taxation and the size of the welfare state - Arnaud Chevalier; Benjamin Elsner; Andreas Lichter; Nico Pestel (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper studies the impact of immigration on public policy setting. We exploit the sudden arrival of eight million forced migrants in West Germany after WWII. These migrants were poorer than the local population but had full voting rights and were eligible for social welfare. We show that cities responded to this shock with selective tax raises and shifts in spending. Voting data suggests that these changes were partly driven by the immigrants' political influence. We further document a strong persistence of the effect. The initial migration shock changed the preferences for redistribution of the following generations.
Keywords: 330